Pengaruh Kepuasan Kerja Terhadap Komitmen Organisasi Karyawan di PT. Ib - Ratna Intan Sari; Alda Ramadhika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the effect of job satisfaction on organizational commitment of employees of PT IB Sayati Bandung. The research method used is quantitative method. The population in this study were all employees of the production department of PT IB as many as 85 employees. The sampling technique used the total sampling method. Data collection through questionnaire distribution, while data analysis techniques using simple linear regression. The results of this study were obtained with a coefficient of determination (R2) of 15.1% of the job satisfaction variable on organizational commitment at PT. IB while the remaining 84.9% was influenced by other variables not examined in this study. It should be concluded that company leaders need to change the strategy of reducing working days because the results of the questionnaire with low scores are on the statement of job satisfaction with the wages received to retain employees so that employees still have a high level of organizational commitment.